The strength of two : a study of effectiveness in peer tutoring to improve the writing of low proficiency students - Chung, Ching Ying. (Universiti Malaysia Sarawak (UNIMAS), 2002)
In Malaysian curriculum, writing is one of the most essential skills. Writing is important in order to pass the SPM writing examinations. Although writing is emphasized in school, students are still having difficulties to write competently. Most of the students are unable to write or make meanings. This study aims to discuss and prove the effectiveness of peer tutoring to improve writing skill ofthe weaker students in an upper secondary school in Kuching. It also looks at the weak students' perceptions or views about pair work and peer tutoring. The subjects of the study were twelve (12) out of twenty-six (26) students selected from Form 4A. The data collected was through marks obtained from the descriptive writing task of the six weak students in both the pair work activity and the peer tutoring activity, semi-structured interview with the six weak students and the observation of the discussion session ofboth pair work and peer tutoring activity. The findings ofthe study showed that students performed better after going through the discussion session of peer tutoring activity compared to after going through the discussion session of pair work activity. Majority of the students expressed their view in favour of peer tutoring rather than pair work approach in helping them with their writing task. Generally, the students prefer the peer tutoring approach. The hypothesis of the study showed that weaker students performed better in descriptive writing task after going through peer tutoring activity compared to pair work activity. The study concluded by suggesting some recommendations based on the findings. The study can be further conducted on the problems faced by teachers when conducting peer tutoring activity in their schools, the problem faced by the tutors and the tutees in using peer tutoring method and others.